Variable high‐pressure and concentration study of cyclohexane pyrolysis at high temperatures. Issue 1 (14th November 2018) - Liszka, Miroslaw Krzysztof; Brezinsky, Kenneth
Abstract: A high‐pressure and temperature cyclohexane pyrolysis shock tube study was completed with the goal of extending the experimental cyclohexane pyrolysis data to pressures relevant to current and future combustors and to investigate whether ring contraction products observed in high‐pressure, supercritical phase cyclohexane and cycloalkane pyrolysis experiments can form at matching, and higher, pressures in the gas phase. The experiments in the current work were completed over a range of 950–1650 K and at nominal pressures of 40, 100, and 200 bar. No alkylcyclopentanes, possible ring contraction products, were observed to form under the conditions of the current study. The production of methylenecyclopentane and 1, 3‐cyclopentadiene, and the other three cyclic species quantified: cyclohexene, benzene, and toluene, increased significantly with a substantial increase in the initial fuel concentration. Two sets of experimental data obtained at 200 bar were compared with a literature and laboratory‐generated model. Both models had difficulty capturing the propadiene and propyne profiles, and the literature model significantly overestimated the benzene observed in the set of experiments completed with the more dilute fuel mixture. The literature model was able to better predict propadiene, propyne, and benzene product profiles in the 200 bar set of experiments, which used a higher concentration of fuel in the test gas. These results suggest that despite both cyclohexane and benzene being well‐studied and important species in combustion chemistry, their reaction pathways and reaction rates would benefit from further refinement.